Ready for first : - Norris, Roy (Macmillan, 2013)
All four skills are systematically developed and practised in each unit, while in-depth exam training is given in the form of regular 'What to expect in the exam' and 'How to go about it' help boxes. This step-by-step approach ensures that students will be fully prepared and confident when sitting the new 2015 First Certificate exam